Digital Governance Model for QR-Based Laboratory Asset Management - Putra Baruna Wijaya; Riki Afriansyah; Eko Sulistyo (Jurnal Inovasi Teknologi Terapan, 2026)
Laboratory asset management in academic environments is commonly administrative and manual, resulting in low efficiency, accountability, and transparency. This study aims to formulate a digital governance model for laboratory asset management through the application of a web-based information system integrated with QR Code technology and automated notifications. The research method involves system design, real-time asset identification implementation, and user acceptance evaluation using User Acceptance Testing (UAT). The results indicate that QR Code and notification integration not only improves operational efficiency but also establishes a structured and traceable asset control mechanism. User satisfaction exceeding 90% confirms that the system supports transparency and accountability principles in laboratory asset governance. This study contributes an applied digital governance principle that can be generalized to other institutional asset management contexts.